1993
DOI: 10.1111/j.1469-7998.1993.tb01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the snow leopard (Panthera uncia) in the Annapurna Conservation Area, Nepal

Abstract: The diet of the snow leopard (Panthera uncia) was studied from 213 scats collected between April 1990 and February 1991 in the Annapurna Conservation Area. Nepal. Seven species of wild and five species of domestic mammals were taken, as well as an unidentified mammal and birds. Blue sheep (Pseudois nayaur) were the most frequently eaten prey. Himalayan marmots (Marmota himalayana) were also important, except in winter when they were hibernating. During winter, snow leopards ate more Royle's pika (Odiotona royk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 5 publications
7
87
3
Order By: Relevance
“…Although in the current study the occurrence of livestock was found in higher proportions of the scats, wild prey also made up a significant proportion of the diet of the snow leopard in Chitral compared to previous studies, i.e. in Manang, Nepal (Oli et al, 1993); Shule Nanshan, China (Schaller et al, 1988); Hemis Ladakh, India (Chundawat and Rawat, 1994); and Pin Valley, India (Bagchi and Mishra, 2006).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Although in the current study the occurrence of livestock was found in higher proportions of the scats, wild prey also made up a significant proportion of the diet of the snow leopard in Chitral compared to previous studies, i.e. in Manang, Nepal (Oli et al, 1993); Shule Nanshan, China (Schaller et al, 1988); Hemis Ladakh, India (Chundawat and Rawat, 1994); and Pin Valley, India (Bagchi and Mishra, 2006).…”
Section: Discussionmentioning
confidence: 57%
“…The current study in Chitral was compared with those from other parts of Asia, such as the Manang region of the Annupurna conservation area in Nepal (Oli, 1993), the Yashu and Shula Nanshan regions of Qinghai Province in China (Schaller et al, 1988), the Hemis region of Ladakh (Chundawat and Rawat, 1994), and the Spiti region in India (Bagchi and Mishra, 2006), as shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the habitat of blue sheep is spaced out in mountainous terrain from the Qilian Mountains in the north to the Himalayas in the south (Aryal et al 2014), which includes Nepal, India, China, Pakistan and Mongolia. Unfortunately, there are no accurate estimates of blue sheep abundance (Schaller 1977;Oli et al 1993). Its other prey species include pika (Ochotona spp.…”
Section: Introductionmentioning
confidence: 99%